THE INFLUENCE OF PRODUCT PLACEMENT ON VIRTUAL INFLUENCER: ANALYSIS OF AUDIENCE ATTITUDES - Natalya, Yenny; Cokki, Cokki (International Journal of Application on Economics and Business, 2025)
This study examines the influence of attitudes towards influencers on attitudes towards product placement and brands, as well as explores the relationship between attitudes towards product placement and Nike brand. Utilizing a sample of 273 students, the research leverages @allysagladys as a virtual influencer on Instagram. The results indicate that attitudes towards influencers affect attitudes towards product placement and brands, while attitudes towards product placement also influence attitudes towards brands. These findings provide valuable insights into understanding the interactions among consumers, influencers, and product placement in the context of social media marketing. The practical implications of these findings can help industry players to optimize their marketing approaches and increase the effectiveness of product promotions through influencers, especially virtual ones.